Romania Financial Sector Assessment Program : Financial Intermediation - World Bank Group (World Bank, Washington, DC, 2018)
Banking financial intermediation relative to the economy is low and declining. The depthof the Romanian banking sector is lagging both in terms of deposit and loan penetration. Cross-cutting factors such as poverty, rurality and informality form a set of constraints that still persist affecting both financial inclusion and intermediation. On the demand side, credit needs remain limited due to low enterprise density, poor health of enterprises, especially micro-enterprises, relatively high number of foreign owned firms, and increasing use of other forms of financing. Furthermore, while economic growth had a positive spillover, this did not translate into a commensurate increase in corporate investment activity. On the supply side, banks have been adversely affected by high Non-Performing Loans (NPLs) and deleveraging pressures. Gaps in access to finance persist, especially for micro, small and medium-sized enterprises (MSMEs), start-ups, and in rural areas. The emergence of banks with niche market positioning could reverse the disintermediation trend, but should be aided by measures to improve the health, performance, and skills of enterprises. Macroprudential measures to protect against excessive sovereign exposures could also, at the margin, support financial intermediation.